Comparative Structural Performance Evaluation of Modified Stopper Mounting Designs in Conveyor Systems Using Finite Element Simulation - Maulidia Hendriani; Andoko Andoko; Riduwan Prasetya; Yahya Zakaria (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
This study investigates the structural performance of three stopper mounting designs for conveyor systems using finite element simulations in ANSYS Workbench. The analysis was conducted using a static structural method, where a vertical downward load of 103.43 N converted from the total weight of the stopper was applied to the structure, and fixed support boundary conditions were assigned at the mounting base. We compared the original design with two modified versions, including one reinforced with stiffening ribs. We evaluated each model under static loads by measuring total deformation, equivalent stress, elastic strain, and safety factor. Compared to the original design, MD 1 reduced total deformation by 88.42%, elastic strain by 53.04%, and equivalent stress by 30.72%, while increasing the safety factor by 0.94%. These improvements were achieved without significantly increasing material usage. The addition of stiffening ribs effectively directed internal forces, stabilized stress zones, and enhanced structural resilience. The original design, while functional, exhibited high deformation and uneven stress distribution that limited its suitability for precision-dependent operations. Reinforcing the geometry proved essential in achieving better mechanical performance and durability. This validates the use of local structural enhancement as a key strategy in mechanical design. The findings contribute to automation system development by highlighting the importance of local reinforcement in precision-oriented automation components.